ANALYSIS OF CATCH PRODUCTIVITY BASED ON DIFFERENCES IN BAGAN SIZE AT UPTD PPP REGION 1 CAROCOK TARUSAN, WEST SUMATRA PROVINCE - Ardelia, Icha Dewi; Ramadan, Fauzan; Heltria, Septy; Ramadhani, Farhan; Afriani, Afriani; Alwi, Yun (Asian Journal of Aquatic Sciences, 2024)
Carocok Tarusan Fishing Port is one of the fishing ports in West Sumatra Province and is a place for fishing activities in Pesisir Selatan Regency with high productivity. Factors that affect the productivity of fishermen include social and economic factors, such as the amount of capital, number of ships, number of workers, distance traveled at sea, and experience. The fishing fleet commonly used is Bagan, with as many as 171 units. Bagan ships in the Carocok Tarusan are dominated by ships measuring ≤30 GT, as many as 162 ships, while those measuring >30 GT are nine ships widely used by fishermen in the Carocok Tarusan Waters are ships measuring ≤30GT. This study aimed to determine the productivity of Bagan Perahu catches based on differences in ship size. This study was conducted from July 2023 to August 2023. The method used in this study was the survey method, with direct observation in the field, conducting interviews with fishermen, and recording the catch using a bagan ship. The types of fish caught using Bagan are Anchovi, Mackerel Scad, and Mackerel Tuna (main catch). Peperek fish, skipjack tuna, Indian Mackerel, Selar fish and Squid (bycatch). Based on the study's results, it can be concluded that in the waters of the Carocok Tarusan, Anchovies are the most commonly caught catch using a boat lift net. Ships measuring 1-10 GT have a higher productivity value than ships measuring 11-20 GT and ships measuring 21-30 GT. With a correlation value (R) approaching 1, the relationship between the dependent variable and the independent variable is stated to be very strong. Meanwhile, the results of multiple linear regression show that 81.14% is influenced by the independent variables (trip, ship size (GT), crew, fuel, and logistics).